Is gaze behaviour in a laboratory context similar to that in real-life? A study in bicyclists. (November 2016) - Zeuwts, Linus; Vansteenkiste, Pieter; Deconinck, Frederik; van Maarseveen, Mariette; Savelsbergh, Geert; Cardon, Greet; Lenoir, Matthieu
Highlights: The trade-off between ecological and internal validity of gaze behaviour was evaluated. Gaze behaviour in the lab and real-life become increasingly comparable with increasing task demand. Experiments in the lab provide useful information regarding visual scanning in real-life. Abstract: Numerous laboratory-based studies recorded eye movements in participants with varying expertise when watching video projections in the lab. Although research in the lab offers the advantage of internal validity, reliability and ethical considerations, ecological validity is often questionable. Therefore the current study compared visual search in 13 adult cyclists, when cycling a real bicycle path and while watching a film clip of the same road. Dwell time towards five Areas of Interest (AOIs) is analysed. Dwell time (%) in the lab and real-life was comparable only for the low quality bicycle path. Both in real-life and the lab, gaze is predominantly driven towards the road. Since gaze behaviour in the lab and real-life tends to be comparable with increasing task-complexity (road quality), it is concluded that under certain task constraints laboratory experiments making use of video clips might provide valuable information regarding gaze behaviour in real-life.